Implementasi Kebijakan Layanan Sistem Informasi Industri Nasional (SIINas) pada Pelaku IKM di Sentra Industri Fashion Seri Kuala Lobam, Kabupaten Bintan - Ajeng Aprianingsih; Afrizal Afrizal; Uly Sophia (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study is backgrounded by the demands of digital transformation in the public administration system through the Electronic-Based Government System (e-government) to achieve effective, transparent, and accountable public services. One of the strategic national instruments is the National Industrial Information System (SIINas), developed by the Ministry of Industry. The main problem in this research is the gap between the national policy on mandatory SIINas reporting and its implementation reality at the local level, where Small and Medium Industries (IKM) actors face technical barriers and digital literacy issues. The objective of this study is to analyze in depth the implementation of the SIINas service policy for IKM actors in the Seri Kuala Lobam Fashion Industry Center, Bintan Regency, in 2025. This research utilizes a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation studies. Data analysis refers to the model by Miles, Huberman, and Saldaña, and is evaluated using six implementation variables by Donald Van Meter and Carl Van Horn. The results show that out of 133 center members, only 17 IKMs have registered SIINas accounts. The main obstacles stem from the low digital literacy of business actors, lack of independent infrastructure, and non-sustainable dissemination efforts. It is concluded that the implementation of the SIINas service is running but not yet optimal, thus requiring intensive mentoring and system refinements to make it more user-friendly.